Industrial-relevant TiO2 types do not promote cytotoxicity in the A549 or TK6 cell lines regardless of cell specific interaction. (September 2022) - Evans, Stephen J.; Lawrence, Rachel L.; Ilett, Martha; Burgum, Michael J.; Meldrum, Kirsty; Hondow, Nicole; Jenkins, Gareth J.; Clift, Martin J.D.; Doak, Shareen H.
Abstract: Due to the expansive application of TiO2 and its variance in physico-chemical characteristics, the toxicological profile of TiO2, in all its various forms, requires evaluation. This study aimed to assess the hazard of five TiO2 particle-types in relation to their cytotoxic profile correlated to their cellular interaction, specifically in human lymphoblast (TK6) and type-II alveolar epithelial (A549) cells. Treatment with the test materials was undertaken at a concentration range of 1–100 μg/cm 2 over 24 and 72 h exposure. TiO2 interaction with both cell types was visualised by transmission electron microscopy, supported by energy-dispersive X-ray. None of the TiO2 materials tested promoted cytotoxicity in either cell type over the concentration and time range studied. All materials were observed to interact with the A549 cells and were further noted to be internalised following 24 h exposure. In contrast, only the pigmentary rutile was internalised by TK6 lymphoblasts after 24 h exposure. Where uptake was observed there was no evidence, as determined by 2D microscopy techniques, of particle localisation within the nucleus of either cell type. This study indicates that industrially relevant TiO2 particles demonstrate cell interactions that are cell-type dependent and do not induce cytotoxicity at the applied dose range. Highlights: Industrial relevant TiO2 did not promote cytotoxicity in A549 or TK6 cells. Rutile TiO2 demonstrated greater potential to undergo cellular association. All test TiO2 types were internalised by A549 cells. Only pigmentary rutile was internalised by TK6 cells. There was no evidence of TiO2 nuclear uptake in either cell types.